PENGARUH JUMLAH PENDUDUK DAN TINGKAT KEMISKINAN TERHADAP KETIMPANGAN PENDAPATAN DI DKI JAKARTA PADA TAHUN 2018 - 2022 - Salsabila, Neng Mutiara; Jaya, Umban Adi (Jurnal Pijar, 2024)
This research aims to determine the effect of population and number of poor people on income inequality in DKI Jakarta. This research uses a quantitative descriptive approach using secondary data from the Central Statistics Agency (BPS). The analysis technique used is multiple regression analysis using SPSS version 25. The research results show that the population variable partially has a negative influence on income inequality with tcount < ttable (-3.461 < 2.037) and a significance value of 0.002 < 0.05. The variable number of poor people partially has a significant effect on income inequality with tcount > ttable (5.089 > 2.037) and a significance value of 0.000 < 0.05. Meanwhile, it is known that the variable number of population (X1) and number of poor people (X2) simultaneously have a significant effect on income inequality with a fcount > ftable value (34.857 > 3.28) and a Sig value. namely 0.000 < 0.05.